Downloading the sky [virtual observatory]. - McDowell, J.C (IEEE spectrum)
An international collaboration of astronomers and computer scientists is piecing together the means to connect all stored data collected over the last several decades by hundreds of ground-based and orbiting observatories in thousands of archives. Their efforts will create the world's biggest and best telescope, known as the Virtual Observatory. VO will allow astronomers, as well as students and the general public to easily locate and download research data over the Internet. VO will also serve as a grid computing network, giving researchers, regardless of location of resources, the equivalent of a supercomputer on their desktops, for comparing billion-record archives or running large-scale simulations. VO encompasses a patchwork of projects organized under the International Virtual Observatory Alliance. The alliance includes more than 200 astronomers and computer scientists in at least 13 countries. Through the VO's various working groups, the scientists are hammering out standards to make the archives interoperable, outlining the necessary IT infrastructure, and defining the VO's scientific goals.